Breaking the Silence: Women’s Resilience and Counter-Hegemonic Agency in Post-Conflict Ambon - Ries Dyah Fitriyah; Iva Yulianti Umdatul Izzah; Afifatur Rohimah; Nihlatul Falasifah (Yayasan Darussalam Bengkulu, 2026)
The article aims to examine the resilience and counter-hegemonic agency of women in Ambon, Indonesia, where communal violence continues to influence their power structures, exclusion, and survival following the conflict there. This study reveals how Ambonese women actively negotiate spaces of agency through strategies that challenge, subvert, and reframe patriarchal and sectarian discourses, while dominant narratives often depict women as passive victims of war or marginalizes in peacebuilding. By combining qualitative descriptive methods and Critical Discourse Analysis (CDA), the research reveals how women transform silence into resistance and vulnerability into resilience through in-depth interviews, life histories, and community observations. In this way, the article links these practices to the theoretical framework of Islamic feminism and Foucault's notion of discourse and power, suggesting that women's agency is not merely a matter of opposition; it involves intricate discussions with cultural, religious, and political structures. Studies indicate that women's efforts, which include grassroots peace activism and reinterpretations of piety and modesty, are counter-hegemonic practices that redefine gendered power relations in post-conflict societies. The inclusion of women's voices as central to sustainable peacebuilding ties the research to further discussions on feminist agency, post-conflict reconstruction, and the politics of resilience.